2007
DOI: 10.1243/09576509jpe436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the volute design parameters on the performance of a centrifugal compressor of an aircraft turbocharger

Abstract: Theoretical and experimental studies on the effect of the volute design parameters on the centrifugal compressor range of stable operation and pressure rise coefficient were investigated. In the theoretical study, the effect of the symmetric and tangent volute area ratios (AR) on the diffuser pressure recovery factor and flow stability was investigated. In the experimental study, different configurations of a symmetrical and tangent (overhung) volutes with different ARs from 0.4 to 0.8 were investigated. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Steglich et al [15] developed an asymmetric diffuser with an internal volute. How different volute design parameters influence performance and efficiency has recently been investigated by several authors [16][17][18][19][20], some of which focused on the tongue area of the volute and how to optimize its design [21,22]. The latest work of Dai et al (2010) showed how different volute designs impact the influence of the volute tongue region on the flow field of a subsonic compressor at off-design conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Steglich et al [15] developed an asymmetric diffuser with an internal volute. How different volute design parameters influence performance and efficiency has recently been investigated by several authors [16][17][18][19][20], some of which focused on the tongue area of the volute and how to optimize its design [21,22]. The latest work of Dai et al (2010) showed how different volute designs impact the influence of the volute tongue region on the flow field of a subsonic compressor at off-design conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Then the data in the file is processed using the Fast Fourier Transformation Analysis (FFT) to estimate the Power Spectrum Density (PSD) by plotting the modified and averaged periodicity of the time-discrete signal vector. The surge point can be obtained using pressure spectrum (analyzing the pressure downstream of the compressor), the frequency peak which describes the surge was between 18 and 22 Hz [17]. Where  is flow coefficient = Q/2πb2r2U2,  is the pressure coefficient =2∆P/ρU2 2 .…”
Section: Experimental Workmentioning
confidence: 99%
“…Jaatinen et al [16] also mentioned that the radial gap ratio has an ideal value and if the radial gap ratio is less than this value, the harm of increased loss will exceed the benefit of reduced slip and blockage. Theoretical analysis was made [17] on a highpressure ratio centrifugal compressor has slotted in the diffuser passages, and the results show that when the mass flow rate decreased, there is flow separation at the angle of the distributor axis, which was eliminated by the slag of the slot length, which was 8-16% of the diffuser chord length, thus increasing the stable flow rate without a significant decrease in the compressor performance. The increasing tip clearance causes additional losses and lowers compressor stage efficiency, especially at higher mass flows [18,19].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…53,54 Volute with tangential inlet gives a favorable performance when compared to symmetric volute. 55 Yang et al 56 suggested a design method to optimize the volute geometry of PAT to enhance its performance. Giosio et al 57 experimented on volute of a commercial PAT with the aim of modifying the inlet flow control.…”
Section: Effects Of Geometric Parameter On the Performance Of A Patmentioning
confidence: 99%